ATTITUDE OF TEACHERS TOWARDS CORPORAL PUNISHMENT IN SECONDARY SCHOOLS IN NSUKKA LGA OF ENUGU STATE - Umeh, Ukamaka L. (International Journal of Human Kinetics, Health and Education, 2023)
The study was conducted to find out the attitude of teachers towards corporal punishment in secondary schools in Nsukka LGA of Enugu State. Three specific objectives with corresponding three research questions, and two null hypotheses guided the study. The study adopted the descriptive research design. Population for the study consisted of 1,313 secondary school teachers in Nsukka LGA. Sample size for the study consisted of 270 teachers selected using multi-stage sampling procedure. Questionnaire served as instrument for data collection. Mean and t-test statistic was used for data analysis. Results among others indicated that secondary school teachers in Nsukka LGA had positive attitude towards corporal punishment, male teachers had more positive attitude towards corporal punishment than the female teachers, and that married teachers indicated more positive attitude than their single colleagues. Also, gender had significant difference in the mean attitude of male and female teachers towards corporal punishment unlike marital status. Based on the findings, the study recommends that corporal punishment should be sustained in secondary schools. However, corporal punishment should not be the order of the day and should not be used to the extreme.